Analisis Bentuk Stimulus, Dimensi Kognitif, dan Karakteristik HOTS pada Instrumen Evaluasi Mata Pelajaran IPA Karya Guru - Fajar Okta Widarta*; Wiwit Artika (Universitas Syiah Kuala, 2021)
The quality of the evaluation instrument describes the quality of learning in schools. Teachers must be able to plan good evaluation instruments. The quality of the evaluation instrument can be assessed from three aspects, including the stimulus, the cognitive dimension, and the characteristics of higher thinking skills (HOTS). This study aims to analyze the teacher's science subject evaluation instrument based on the form of stimulus, cognitive dimensions, and HOTS characteristics. This research is descriptive quantitative, where the data is presented as a percentage and then described. Qualitative tests on the content of the stimulus are used to group the items into a certain stimulus form. The cognitive process dimension identification sheet was developed based on Bloom's revised taxonomy. The classification of HOTS questions uses the HOTS characteristic identification criteria. The results showed that most of the questions made by the teacher did not have a stimulus, the distribution of the cognitive process dimensions of the questions was uneven, and the questions made were not HOTS. Based on the results of the analysis, it is concluded that the teacher's evaluation instrument was poor